2022
DOI: 10.1596/1813-9450-9991
|View full text |Cite
|
Sign up to set email alerts
|

Globally Engaged Firms in the COVID-19 Crisis

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Empirical evidence confirms that, during the COVID-19 pandemic, international supply chains sheltered firms and countries from shortages, thereby contributing to their resilience (Giglioli et al, 2021). Globally engaged firms recovered faster, due to their higher capabilities and their capacity to adjust (Constantinescu et al, 2022). On the anniversary of the Russian invasion of Ukraine, the WTO reported that international supply chains also offered flexibility and adjustment channels to the shock, and that resilience came from the ability to trade (Ossa, 2023).…”
Section: Myth 3: Foreign Supply Makes Supply Chains Less Resilientmentioning
confidence: 99%
“…Empirical evidence confirms that, during the COVID-19 pandemic, international supply chains sheltered firms and countries from shortages, thereby contributing to their resilience (Giglioli et al, 2021). Globally engaged firms recovered faster, due to their higher capabilities and their capacity to adjust (Constantinescu et al, 2022). On the anniversary of the Russian invasion of Ukraine, the WTO reported that international supply chains also offered flexibility and adjustment channels to the shock, and that resilience came from the ability to trade (Ossa, 2023).…”
Section: Myth 3: Foreign Supply Makes Supply Chains Less Resilientmentioning
confidence: 99%
“…Constantinescu et al (2022) use a different perspective to assess the effect of firm-level international trade. Analysing firm-level data from 45 countries, they find that 'globally engaged firms' (firms directly involved with international markets) are characterised by a faster recovery.…”
mentioning
confidence: 99%